Region around the North Pole : giving the records of the most important Explorations. - Century Company. http://id.loc.gov/authorities/names/n81038526 http://viaf.org/viaf/sourceID/LC|n81038526; Matthews-Northrup Company. http://id.loc.gov/authorities/names/n50006564 http://viaf.org/viaf/sourceID/LC|n50006564 (UM Clark Library Maps, 1897)
Relief shown by hachures, and bathymetery soundings and shading.; Text on verso.; Insets: Franz Josef Land -- Spitzbergen -- Smith Sound and Robeson channel.; No. 3 from The Century Atlas. 1 map : col. 27 x 39 cm